Best Fit versus Default Distribution and the Impact on the Reliability over the Design Lifetime of Hydraulic Structures - Krimil, Farida; Bouchahm, Nora; Tebbi, Fatima Zohra (Engineering, Technology & Applied Science Research, 2023)
In the present study, Flood Frequency Analysis (FFA) is performed on the daily inflows of a reservoir dam taken as a case study. The Peaks-Over-Threshold (POT) approach was adopted. A comparison between the default generalized Pareto distribution and the best distribution fitted to the data has been carried out. After the risk analysis, the reliability of the structure decreases to 25.60% for the chosen threshold values if the best distribution is adopted instead of the default fit.